Studi Kasus Karakteristik Penderita Kanker Paru Di Ruang Rawat Jasmin RSUD Arifin Achmad Provinsi Riau: karakteristik kanker paru - Ningrum, Trisiwi Kusuma; Maswarni; Gasril, Pratiwi; Shofia (As-Shiha: Jurnal Kesehatan, 2023)
Lung cancer is the uncontrolled growth of abnormal cells in one or both lungs. According to the World Health Organization (WHO) lung cancer is the leading cause of death in the cancer group. various risk factors, especially smoking is the main cause of lung cancer. The purpose of this study was to determine the characteristics of patients with lung cancer in the Jasmin ward of Arifin Achmad Hospital, Riau Province. The research design used was descriptive research with a sample size of 21 respondents. The sampling technique used accidental sampling technique. The instruments used were questionnaires and check list sheets with univariate data analysis. The results showed that patients with lung cancer in the Jasmine ward of Arifin Achmad Hospital Riau Province with age distribution showed the lowest age of 23 years and the highest age of 77 years. Based on gender, the male group suffered the most, namely 16 people (76.2%). The majority of patients with lung cancer are patients who have a history of smoking, namely 14 respondents (66.7%). A total of 17 respondents (81.0%) patients had never had a previous lung infection. lung cancer patients the majority of patients had never had a previous lung infection as many as 17 respondents (81.0%). Based on the distribution of occupations, the most suffered by self-employed with a total of 4 respondents (19.0%). Patients with lung cancer who were not exposed to pollution were 14 respondents (66.7%). It is hoped that there will be an early lung cancer screening movement and primary and secondary prevention efforts, one of which is an effort to reduce smoking rates in Indonesia as a top priority to reduce the incidence of lung cancer.